ASME 2010 3rd Joint US-European Fluids Engineering Summer Meeting: Volume 1, Symposia – Parts A, B, and C 2010
DOI: 10.1115/fedsm-icnmm2010-31026
|View full text |Cite
|
Sign up to set email alerts
|

Reynolds Number Dependence for Laminar Flow Loss Coefficients in Tee and Wye Junctions

Abstract: In fluid flow piping systems, tee and wye junctions are commonly encountered and the study of flow through them has been well documented. Most of these studies have focused on flow characterized as turbulent for which there are nearly constant losses in pressure and kinetic energy in the junctions. Laminar flow has received much less attention since it is not frequently observed in macro scale piping systems where pipe diameters are measured in centimeters. The recent increase in use of micro scale flow device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
3
3
0
Order By: Relevance
“…Kiser et al . reported results of a CFD study that suggested K ∼ 1 for 200 < R e < 2000 (in agreement with our results). However, for R e < 200, an inverse relationship with R e was found, with K reaching 300‐400 at R e = 1.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Kiser et al . reported results of a CFD study that suggested K ∼ 1 for 200 < R e < 2000 (in agreement with our results). However, for R e < 200, an inverse relationship with R e was found, with K reaching 300‐400 at R e = 1.…”
Section: Discussionsupporting
confidence: 93%
“…The majority of work relating to junction loss coefficients has been devoted to high Re flow, but a few investigators have studied junction losses at low Re, which may be of interest in micro-scale flow devices. Kiser et al [56] reported results of a CFD study that suggested K 1 for 200 < Re < 2000 (in agreement with our results). However, for Re < 200, an inverse relationship with Re was found, with K reaching 300-400 at Re D 1.…”
Section: Low Reynolds Numberssupporting
confidence: 92%
See 3 more Smart Citations